Van briefwisseling tot tijdschrift - Stijn Vanclooster (Contextes)
Today, Van Nu en Straks is still known as one of the most revolutionary periodicals in the Flemish literary history. Extensive recent research invite to review that image. The highly revolutionary image of the journal seems to a large extent connected with statements from the protagonists in the periodical itself. Recent studies show that Van Nu en Straks reflected a tradition and that the periodical was influenced by certain literary examples. One of them was Henrik Ibsen. The Ibsen-case is a concrete example on the domain of reception and influence where Van Nu en Straks had a unique position, and illustrates thereby how revealing correspondence can be for the study of literary periodicals. Such more contextualizing studies go hand in hand with the broad-cultural approach which characterizes literary historiography nowadays and which has also found acceptance in the Low Countries. There, the insights of the New Historicism could be useful.